Integrating Cognitive and Affective Dimensions of Pain Experience into Health Professions Education - Beth B Murinson; Lina Mezei; Elizabeth Nenortas (Pain Research and Management)
Pain is prevalent in clinical settings, and yet it is relatively under-represented in the education of most students in the health professions. Because pain includes both sensory-discriminative and affective features, teaching students about pain presents unique challenges and opportunities. The present article describes the evolution of a new blueprint for clinical excellence that, among other competencies, incorporates a need for the emotional development of clinical trainees. The framework has been applied to the development and implementation of two new courses in pain. The first course is designed to provide a comprehensive foundation of medical knowledge regarding pain, while integratively introducing students to the affective dimensions of pain. The second course is designed to enhance students’ appreciation for the protean effects of pain through use of the humanities to represent medical experience. It is concluded that, to be most effective, fostering the emotional development of trainees in the health professions necessitates the incorporation of affect-focused learning objectives, educational tasks and assessment methods.